The Microelectronic Transducers of Pressure with the Frequency Output - Osadchuk, V. S.; Osadchuk А. V. (Elektronika ir Elektrotechnika, 2012)
In the given article the possibility of making the microelectronic transducer of pressure with a frequency output signal is shown on the basis of the autogenerating arrangement which will consist of bipolar transistor and MOSFET transistor. The change of pressure of bipolar transistor is proportionally the frequency generation. Analytical dependencies of function transformation and sensitivity are received. The deformation changes of the parameters tensiosensitivity bipolar transistor are designed. Sensitivity of the arrangement 2,0-4,25 kHz / Pa·105. Ill. 9, bibl. 14 (in English; abstracts in English and Lithuanian). DOI: http://dx.doi.org/10.5755/j01.eee.121.5.1661